2022
DOI: 10.1155/2022/4978556
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effect of Tetrahydrocurcumin on Pseudomonas aeruginosa Lipopolysaccharide-Induced Inflammation by Suppressing JAK/STAT and Nrf2/HO-1 Pathways in Microglial Cells

Abstract: Brain inflammation, a pathological feature of neurodegenerative disorders, exhibits elevated microglial activity and increased levels of inflammatory factors. The present study was aimed at assessing the anti-inflammatory response of tetrahydrocurcumin (THC), the primary hydrogenated metabolite of curcumin, which was applied to treat Pseudomonas aeruginosa (P.a.) lipopolysaccharide- (LPS-) stimulated BV2 microglial cells. THC reduced P.a. LPS–induced mortality and the production of inflammatory mediators IL-6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…These were then sorted by the number of target proteins (counts) in the pathways to screen the top 40 pathways (Figure S1B). Based on the literature, we found that the HIF-1, 34 TNF, 35 PI3K/AKT, 36 IL-17, 37 VEGF, 37 and JAK/STAT signaling pathways 38,39 were involved in the regulation of microgliamediated inflammatory responses. Accordingly, we initially selected these six signaling pathways for further study.…”
Section: Alpinetin Reduced the Levels Of Proinflammatory Cytokines In...mentioning
confidence: 99%
“…These were then sorted by the number of target proteins (counts) in the pathways to screen the top 40 pathways (Figure S1B). Based on the literature, we found that the HIF-1, 34 TNF, 35 PI3K/AKT, 36 IL-17, 37 VEGF, 37 and JAK/STAT signaling pathways 38,39 were involved in the regulation of microgliamediated inflammatory responses. Accordingly, we initially selected these six signaling pathways for further study.…”
Section: Alpinetin Reduced the Levels Of Proinflammatory Cytokines In...mentioning
confidence: 99%
“…Curcumin has been shown to be effective in improving pathological features and preventing the development of various diseases. It also modulates inflammatory and metabolic processes to protect cells from oxidative stress ( Lin et al, 2022 ). This section elaborates on several pathways and factors that enhance cell synaptic plasticity, microglia phenotype, and gut microbiota involving curcumin.…”
Section: Neuroprotective Functions and Mechanisms Of Curcuminmentioning
confidence: 99%
“…The process of microglial inflammation is characterized by aberration and alternation of various intercellular neuroinflammatory cascades, among which the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) signaling and nuclear factor erythroid 2-related factor (Nrf2) signaling are increasingly recognized as potential targets for battling against microglial inflammation. In the CNS, excessive phosphorylation of JAK and STAT causes a pleiotropic cellular cascade, which is implicated in activating microglial cells responsible for the release of various inflammatory cytokines. , Correspondingly, the outcomes of many studies have shown that suppressing JAK/STAT signaling potently reduces microglial inflammation. By contrast, convergent evidence indicates that Nrf2 is a redox-sensitive transcription factor that helps microglial cells adapt to deleterious oxidative stress and neuroinflammation by the upregulation of a great number of cytoprotective genes including heme oxygenase-1 (HO-1); nevertheless, these endogenous feedback alternations on Nrf2 signaling are always insufficient to block the pathological progress. In fact, further boosting the Nrf2 signaling by therapeutic agents has been well proven to potently reduce the expression of several proinflammatory genes including TNF-α and IL-6, resulting in decreased microglial neuroinflammation. , Taken together, the critical roles of JAK/STAT and Nrf2 signaling pathways and their relative independent mechanisms may pave the way to synergistically manage microglial inflammation and emerge as a promising strategy to delay the progression of inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%